Flypaper Effect: Fiscal Illusion and Bureaucratic Model - Hendra Kusuma (Jurnal Ekonomi dan Studi Pembangunan, 2017)
Fiscal decentralization as a delegation form of fiscal authority from the central government to the regional government is expected to accelerate the regional economic growth in accordance with the respective characters in each region. The overspreading potency in utilizing the transfer funds from the central government is more likely to be higher if the regional budget is not designed effectively and efficiently to support the acceleration of regional economic activities. This study aimed at investigating the influence of unconditional grant, regional revenue, gross regional domestic product, and population density towards the regional budget in East Java Province during the implementation of fiscal decentralization. Model specification used was an overview of regional budget, in which the flypaper effect was detected by comparing the coefficient of unconditional grant regression and the regional revenue. It was done by using econometric-model panel data for 33 districts in East Java Province during 2001 – 2005. By using fixed-effect model estimation, this study figured out that there was a flypaper effect indicated by the higher elasticity number of unconditional grant than of regional revenue towards the regional budget in East Java Province.Keywords: fiscal decentralization, flypaper effect, panel data analysisJEL Classification: C23, E62